EPISODE PERJUANGAN BANGSA DALAM JURNALISME KORAN JAWA POS DALAM RUBIK “HOAX ATAU BUKAN” - Aditya, Krisna (LEMBAGA PUSAT KAJIAN KEBANGSAAN/PUSKAB UKRI, 2024)
In an era when information does not only come from journalists, but also from various media platforms and even from ordinary people, there is a lot that we consider as